Living a healthy life : an evaluation of a self-management for chronic conditions course, Arthritis New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science (Health Psychology) at Massey University - Pretorius, Charlene (Massey University, 2004)
Chronic disease management is a major challenge for health care systems in the developed world. Self-management has the ability to help improve health status, health behaviours and reduce health care utilisation for people with chronic disease. In this exploratory before-after cohort study, questionnaires were distributed to people with chronic disease attending a self-management course offered by Arthritis New Zealand. Ninety-four people at baseline, and at six months, 67 people, completed eight health status, four health behaviour, one self-efficacy, and six health care utilisation measures. The 67 participants at six months also completed seven course evaluation measures in addition to course delivery, social support, course barrier and course attendance measures. The relationship at onset between self-efficacy and health status was analysed using a stepwise regression. Self-efficacy, which accounted for 27% of variance, was significantly related to health distress and to the energy levels of participants. To determine the relationship between self-efficacy and self-management behaviours at baseline, standard multiple regressions were run. Self-efficacy was unrelated to the self- management behaviours of the participants at the course onset. To analyse the mediation effect of self-efficacy on health status a stepwise regression was run, while holding self-efficacy constant. Self-efficacy at six months explained 42% of the variance in baseline self-efficacy, after controlling for baseline self-efficacy in the second model, self-efficacy at six months was significantly related to perceived illness intrusiveness and accounted for an additional 58% of the variance. Two hierarchical stepwise-regressions assessed the mediation effect of self-efficacy on self-management behaviours. Self-efficacy at six months accounted for no additional variance in the participants' self-management skills. Paired t-tests and Wilcoxon matched-pairs signed ranks measured changes in health status, self-efficacy, health behaviours and health care utilisation. No significant improvements occurred in health status. Significant improvements occurred in four health outcomes. Independent t-tests and the Mann- Whitney tests identified significant differences between gender, age and location with health status, health behaviour and health care utilisation outcomes at baseline and at six months. The process evaluation of the course showed general satisfaction. Explanations for the results are offered, limitations of the study are highlighted, and suggestions for future chronic disease self-management research are proposed.
Keywords: New Zealand; Self-efficacy; Self-management (Psychology); Self-care, Health; Chronically ill; Chronically ill -- Psychological aspects; Arthritis New Zealand (Organization)